ARGrocery: An Augmented Reality-Assisted grocery shopping mobile application - Yew, Jun Yi (2023)
In the context of grocery shopping, making judgments about what to buy at physical stores may be difficult since there are so many options that are comparable. Hence, people typically spend a lot of time in the store in reading the ingredient labels on the nutritional information on the packaging to pick the best product they desire. Even while it takes time, the primary challenge for shoppers, especially those who are allergic to a particular component, is that they find it difficult to filter and look for items that are completely devoid of all allergenic substances. In this paper, a mobile application that uses Augmented Reality (AR) technology to identify products, display product information, and perform ingredient filtering is proposed to assist shoppers in decision-making. The system utilized marker-based AR to identify the product with a smartphone camera and display the product information such as product name, brand, and ingredient list. Furthermore, the proposed system uses AR tags with colours to make it easier for users to recognise and differentiate both suitable and not suitable products. This project is beneficial for shoppers to have a richer shopping experience with more comprehensive and detailed realistic commodity information by using AR technology with a mobile phone.